2007
DOI: 10.1080/09064710500517865
|View full text |Cite
|
Sign up to set email alerts
|

Scandinavian colonial bentgrass diversity described by RAPD, variable chlorophyll fluorescence, and collecting site ecogeography

Abstract: Scant information is available describing the diversity of colonial bentgrass (Agrostis capillaris L.) accessions, particularly from boreal and sub-polar ecoregions. In this study, we have compared the diversity of 18 Scandinavian accessions with three ecologically diverse accessions from more southern latitudes. Two of three Scandinavian pools overlapped in the humid temperate boreal ecoregion, and a third pool coincided with the Subarctic Continental Boreal ecoregion. The fourth pool comprised the three lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…This is consistent with existing research on U.S. cotton cultivars (Burke, 1990;Mahan, 2000;Wanjura et al, 1990Wanjura et al, , 1992. Although genotypic variation in chlorophyll fl uorescence recovery rates can be observed in G. hirsutum between genotypes of diff erent thermotolerances (Snider et al, 2010) and in other species (Karlsen and Steiner, 2007), the Australian cultivar Sicot 70BRF gave similar results to the historically studied U.S. cultivars Paymaster 145 and Paymaster HS26.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with existing research on U.S. cotton cultivars (Burke, 1990;Mahan, 2000;Wanjura et al, 1990Wanjura et al, , 1992. Although genotypic variation in chlorophyll fl uorescence recovery rates can be observed in G. hirsutum between genotypes of diff erent thermotolerances (Snider et al, 2010) and in other species (Karlsen and Steiner, 2007), the Australian cultivar Sicot 70BRF gave similar results to the historically studied U.S. cultivars Paymaster 145 and Paymaster HS26.…”
Section: Discussionsupporting
confidence: 90%
“…Zhao et al (2006) found the amount of genetic similarity (GS) averaged between 0.51 and 0.63 within this set of A. capillaris, suggesting that this material may be a source of genetic diversity. Karlsen and Steiner (2007) used random amplifi ed polymorphic DNA markers to assess the genetic diversity in a set of 18 Scandinavian colonial bentgrass accessions. Similarity ranged from 0.23 to 0.84, and based on marker clustering, three major groups were formed.…”
mentioning
confidence: 99%